Embarking on Friendship: Exploring Early Soviet-Indian Relations - S. I. Lunev (Vestnik MGIMO-Universiteta)
By the onset of the Second World War, the USSR had virtually no experience or established traditions of interaction with South Asian countries. Initially, Soviet-Indian relations could be characterized as tepid, largely due to a lack of accurate information about each other. During the wartime, the USSR underestimated the advantages of forging close ties with Indian left-wing centrists, favoring instead communists who provided the Kremlin with falsified data on the national liberation movement in the country.The article examines how bilateral relations evolved and strengthened as mutual knowledge grew. The second stage of Soviet-Indian relations (1955-1971) can be termed as a period of "birth of friendship," as the image of partnership is consolidated in the eyes of Soviet and Indian politicians and the public. Soviet diplomacy played a pivotal role in shaping policy changes: diplomats sought to gather crucial information about events in the country, transmit it to the USSR, and promote bilateral rapprochement, sometimes even acting in violation of instructions.The article pays particular attention to the activities of Subhas Chandra Bose, the leader of the left wing of the Indian National Congress, who according to Indian sociological surveys on the most prominent politicians of the 20th century, ranks second only to Mahatma Gandhi. During the Second World War, he was an uncompromising fighter against British colonialists. The Soviet Union did not pay sufficient attention to S.C. Bose, although he potentially could have been a valuable partner for Moscow.At present, the problem of mutual lack of awareness has resurfaced, hindering the development of closer political, economic, and cultural-humanitarian ties between Russia and India.